Evangelical Christianity and democracy in Africa - Ranger, Terence O. (Evangelical Christianity and democracy in the Global South, 2008)
This is one of four projected volumes to emerge from a massive, Pew-funded study that sought to answer the question: What happens when a revivalist religion based on scriptural orthodoxy participates in the volatile politics of the Third World? Is the result a democratic politics of the ballot box, or is it more like an authoritarian politics of command from on high? Does the evangelical faith of the Bible hinder or promote a politics of the ballot box? At a time when the global-political impact of another revivalist and scriptural religion, Islam, fuels vexed debate among analysts the world over, these volumes offer an unusual comparative perspective on a critical issue: the often combustible interaction of resurgent religion and the developing world's unstable politics.The present volume considers the case of Africa, the region with the world's fastest expanding population.